2022
DOI: 10.3389/fped.2022.884539
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1: A Potential Target of Nervus Vagus Stimulation in Pediatric SARS-CoV-2-Induced ALI/ARDS

Abstract: From the start of pandemics, children were described as the ones who were less affected by SARS-Cov-2 or COVID-19, which was mild in most of the cases. However, with the growing vaccination rate of the adult population, children became more exposed to the virus and more cases of severe SARS-CoV-2-induced ARDS are being diagnosed with the disabling consequences or lethal outcomes associated with the cytokine storm. Thus, we do hypothesize that some of the children could benefit from nervus vagus stimulation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Moreover, in this study, the confounding factors were not adjusted during the perioperative period. Pediatric patients are more susceptible to surgical stress, ischemia-reperfusion, and the effects of anesthesia drugs and long-term mechanical ventilation because of the specific pediatric immunity state and anatomical features of the respiratory system [ 17 ]. As a result, children are more vulnerable to perioperative lung injury than adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in this study, the confounding factors were not adjusted during the perioperative period. Pediatric patients are more susceptible to surgical stress, ischemia-reperfusion, and the effects of anesthesia drugs and long-term mechanical ventilation because of the specific pediatric immunity state and anatomical features of the respiratory system [ 17 ]. As a result, children are more vulnerable to perioperative lung injury than adults.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extensive studies have demonstrated that plasma HMGB1 level is a sensitive indicator of acute respiratory distress syndrome (ARDS) [ 14 ]. HMGB1 is a central mediator of lethal inflammation and could be a potential target for innovative therapeutic strategies for COVID-19 [ 15 , 16 ], even in the pediatric field [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pathway bridges the autonomic nervous system and immune system. Recently, the alleviating effect of COVID-19-induced hyperinflammation has been widely described in several studies (115,117,(121)(122)(123). Under direct activation of the afferent vagal nerve, the main neurotransmitter ACh is released which further stimulates α7nAChR (124,125) resulting in an anti-inflammatory response.…”
Section: The Cholinergic System α Nachr and Platelet Role In Covid-in...mentioning
confidence: 99%
“…PANoptosis is a complex form of inflammatory programmed cell death (PCD) pathway that involves pyroptosis, apoptosis, and necroptosis, whereas it cannot be characterized by any of these three PCD pathways alone. , PANoptosis has been elucidated in a variety of conditions ranging from normal development to microbial infectious, autoimmune diseases, cytokine storm, and cancer. Previous studies have shown that PANoptosis was closely related to lung injury. , During severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, patients develop systemic symptoms of varying severity and induce PANoptosis, leading to further exacerbation of the pulmonary cytokine storm, and COVID-19-associated pneumonia can progress to ARDS. ,, Because of the complexity of PANoptosis, the treatment maybe fails if three PCDs in PANoptosis cannot be simultaneously inhibited to prevent the compensatory activation of other pathways. However, no research focused on a certain drug or treatment to simultaneously inhibit the three arms of PANoptosis process in ALI.…”
Section: Introductionmentioning
confidence: 99%
“…3,15 During severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, patients develop systemic symptoms of varying severity and induce PANoptosis, leading to further exacerbation of the pulmonary cytokine storm, and COVID-19associated pneumonia can progress to ARDS. 5,16,17 Because of the complexity of PANoptosis, the treatment maybe fails if three PCDs in PANoptosis cannot be simultaneously inhibited to prevent the compensatory activation of other pathways.…”
Section: ■ Introductionmentioning
confidence: 99%